An Ovidian Poetics of Exile: Renaissance Crossovers with the Tristia - Sophie Jane Buckingham (Janeway JS, 2019)
This article foregrounds some of the basic principles contained within Ovid’s Tristia, a series of epistles written whilst he was exiled from Augustan Rome in A.D. 8. It seeks to find nuances and reapplications of this long-overlooked work in Renaissance England, and looks at translation practice and poets of the sixteenth century who were indebted to Ovid’s ‘exile poetics’ in their own compositions.
Keywords: archive; canon; women& #x27; s writing; Alcott; biography